2018
DOI: 10.1016/j.measurement.2018.05.056
|View full text |Cite
|
Sign up to set email alerts
|

Traceable sea water temperature measurements performed by optical fibers

Abstract: This paper describes a technique to perform traceable temperature measurements of the seawater column and seawater surface, based on optical fiber Bragg gratings. The paper explains the different phases of the work done: design of the optical fibers, its optical and thermal calibration and onsite measurements of the seawater temperature. In the design of these thermometers, special attention was paid to the involved materials in order to prevent any damage due to the exposure to such rugged environment. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…A narrow range of wavelengths is reflected from a sensor when it is illuminated by broadband light from the demodulator. The light reflected is sent to the demodulator device, which determines the temperature along the length of the detection tube, thus tracking the temperature of the wall joint [ 26 , 28 , 29 ].…”
Section: Detection Methods and Established Systemmentioning
confidence: 99%
“…A narrow range of wavelengths is reflected from a sensor when it is illuminated by broadband light from the demodulator. The light reflected is sent to the demodulator device, which determines the temperature along the length of the detection tube, thus tracking the temperature of the wall joint [ 26 , 28 , 29 ].…”
Section: Detection Methods and Established Systemmentioning
confidence: 99%
“…By comparing the measured results with CTD (YRS1-1), measurement accuracy better than 0.2 °C was obtained. In 2017, C. Garcia Izquierdo et al also demonstrated a distributed temperature sensor monitoring system, in which an FBG was written into the single-mode fiber coated with acrylates (SM-ITU652) [ 144 ]. To enhance its environmental adaptability, the fiber-optic sensor was encapsulated in a 316L stainless steel tube with a seawater-resistant (polypropylene/PEEK) coating.…”
Section: Practical Application Of Optical Fiber Sensors In Ocean Obse...mentioning
confidence: 99%
“…A new technique to perform traceable temperature measurements in seawater was studied, designed, developed and tested in field by CEM, CSIC and UPC [24,25]. The thermometers consist of several FBGs installed at different points along the optical fibers.…”
Section: Experimental Sea Temperature Performed By Fiber Opticsmentioning
confidence: 99%
“…A new technique to perform traceable temperature measurements in seawater was studied, designed, developed and tested in the field by CEM, CSIC and UPC [24,25].…”
Section: Experimental Sea Temperature Measurements Performed By Fiber...mentioning
confidence: 99%
See 1 more Smart Citation